Ethnomathematical Exploration of Geometric Forms in the Rawagede Monument, Karawang - Puspita, Ayu Dian; Ayu Fitri; Yulistina Nur Ds (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Education and culture are inseparable aspects of daily life. Ethnomathematics is a field that bridges mathematics and culture, particularly in the context of mathematics education. Unconsciously, people engage in various activities involving basic mathematical concepts and ideas such as counting numbers, measuring, arts, games, trading, and architectural design. This study aims to examine and explore the ethnomathematics of the Rawagede Monument in Karawang in order to gather foundational information for the development of ethnomathematics in the teaching of plane geometry, as reflected in the form of the Rawagede Monument. This research is exploratory in nature and uses a descriptive qualitative approach. Based on the results of the study, there are mathematical elements and concepts embedded in the construction of the Rawagede Monument. The mathematical concept identified in the Rawagede Monument is plane geometry.